Sosialisasi tentang Pengaruh Buruk Pinjol Agar Masyarakat Lebih Sadar dan Waspada Khususnya di Wilayah Sukodono Kabupaten Sidoarjo - Gusti Ananda Syalum Saputra (Jurnal Pengabdian Masyarakat (Bisma), 2026)
The rapid pace of financial technology innovation has fueled a trend toward online loans, which, unfortunately, is often accompanied by risks such as high interest rates, aggressive debt collection practices, and data privacy violations. A lack of financial literacy is the primary factor driving people to fall into the trap of illegal online lending practices. To address this, a community service program was implemented in Sukodono, Sidoarjo, to educate residents about the risks of online lending using the Asset-Based Community Development (ABCD) method. Through a systematic process ranging from identification to evaluation, this program successfully improved residents' financial literacy, fostered more prudent financial management practices, and strengthened social solidarity in the face of threats posed by illegal financial services.